Heterogeneity in the Effect of Home Energy Audits: Theory and Evidence - Manuel Frondel; Colin Vance (Environmental and Resource Economics, 2013)
A longstanding question in the study of energy demand concerns the role of information as a determinant of home efficiency improvements. Although the provision of information via energy audits is frequently asserted to be an effective means for governments to encourage the implementation of efficiency-enhancing renovations, empirical support for this assertion is tenuous at best. Apart from endogeneity issues with respect to receiving an audit, two other factors have complicated attempts to measure their effect: First, the nature of the information provided by the audit is typically unobserved, and, second, the response to this information may vary over households. Using household data from Germany, we address both sources of heterogeneity by estimating a random-parameter model of four retrofitting alternatives. In addition to confirming the importance of costs and savings as determinants of renovation choices, our results suggest that the effects of consultancy vary substantially across households, with some households responding negatively to the provision of information.
Keywords: C35; D81; Q41; 330; Energy audit; Environmental policy; Mixed logit; Random-coefficient models